2012
DOI: 10.1093/ndt/gfs337
|View full text |Cite
|
Sign up to set email alerts
|

Growth arrest-specific gene 6 (Gas6) levels are elevated in patients with chronic renal failure

Abstract: Dysregulation of circulating Gas6 is associated with renal disease and inversely proportional to renal function. Low albumin and higher IV iron administration were associated with higher Gas6 levels, suggesting a possible connection between inflammation and oxidative stress mediated by iron. Protein S levels were also elevated in CKD patients, but the relevance of this finding needs to be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 44 publications
2
40
1
Order By: Relevance
“…We confirmed higher values of both GAS6 and sMerTK in patients with renal failure. In accordance with these findings, higher values of GAS6 have been reported in chronic renal failure [33]. The sMerTK values seem linked to kidney disease, as the increase was mainly in patients with renal failure.…”
Section: Discussionsupporting
confidence: 72%
“…We confirmed higher values of both GAS6 and sMerTK in patients with renal failure. In accordance with these findings, higher values of GAS6 have been reported in chronic renal failure [33]. The sMerTK values seem linked to kidney disease, as the increase was mainly in patients with renal failure.…”
Section: Discussionsupporting
confidence: 72%
“…In vitro stimulation of vascular smooth muscle cells or immortalized human mesangial cells with AngII induced Gas6 and Axl expression via NADPH-oxidase 17 . A more recent clinical study 18 demonstrated that circulating Gas6 is associated with renal disease severity and Gas6 levels were inversely correlated with kidney function in patients with end-stage renal disease. Likewise, in recipient Axl−/− chimeras the increases in kidney Gas6 mRNA levels showed greater ROS in kidneys during early phase of DOCA-salt.…”
Section: Discussionmentioning
confidence: 99%
“…After informed consent, blood samples were collected from 6 healthy donors with normal kidney function and 20 patients with end-stage renal disease who were on hemodialysis (HD). Blood was collected prior to the routine HD session [30]. Blood samples were centrifuged at 3000 rpm, and the sera were aliquoted and stored at −80C.…”
Section: Methodsmentioning
confidence: 99%